2012
DOI: 10.2147/ijn.s26679
|View full text |Cite
|
Sign up to set email alerts
|

The use of quartz crystal microbalance with dissipation (QCM-D) for studying nanoparticle-induced platelet aggregation

Abstract: Abstract:Interactions between blood platelets and nanoparticles have both pharmacological and toxicological significance and may lead to platelet activation and aggregation. Platelet aggregation is usually studied using light aggregometer that neither mimics the conditions found in human microvasculature nor detects microaggregates. A new method for the measurement of platelet microaggregation under flow conditions using a commercially available quartz crystal microbalance with dissipation (QCM-D) has recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 36 publications
(42 reference statements)
1
42
0
Order By: Relevance
“…12,13 In addition, we have recently demonstrated that NP-induced platelet aggregation can be detected using QCM-D at NP concentrations that are undetectable by flow cytometry and light transmission aggregometry, both of which are wellestablished methods for measurement of platelet activation and aggregation. 14,15 Although still considered the "gold standard" for testing platelet function, light transmission aggregometry is relatively non-physiological because separated platelets are usually stirred under low shear stress and only form macroaggregates after addition of agonists, ie, conditions that do not accurately mimic platelet adhesion, activation, or aggregation in response to vessel wall damage. 16 The objective of this work was to investigate whether or not this novel approach could also be used to unravel the pharmacology and platelet aggregation pathways that underlie the interactions between NPs and platelets.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, we have recently demonstrated that NP-induced platelet aggregation can be detected using QCM-D at NP concentrations that are undetectable by flow cytometry and light transmission aggregometry, both of which are wellestablished methods for measurement of platelet activation and aggregation. 14,15 Although still considered the "gold standard" for testing platelet function, light transmission aggregometry is relatively non-physiological because separated platelets are usually stirred under low shear stress and only form macroaggregates after addition of agonists, ie, conditions that do not accurately mimic platelet adhesion, activation, or aggregation in response to vessel wall damage. 16 The objective of this work was to investigate whether or not this novel approach could also be used to unravel the pharmacology and platelet aggregation pathways that underlie the interactions between NPs and platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation, P-selectin mobilizes to the surface membrane of the activated platelets, is shed from the platelet surface to form sP-selectin, and is released into the bloodstream. [26][27][28][29] The increase of circulation concentration of sP-selectin plays a core role in thrombosis, and inhibition of sP-selectin production has been considered one of the principal mechanisms of antithrombotic agents. Therefore, Figure 3 depicts concentration dependence of AERL inhibiting AA-activated platelets from releasing sP-selectin and discloses a possible mechanism of action of AERL offering in vitro antiplatelet aggregation and in vivo antithrombotic action.…”
Section: Discussionmentioning
confidence: 99%
“…This is the result of attempts to deliver larger amounts of PS selectively to the cell, e.g., in nanoaggregates such as liposomes, to use the enhanced permeability and retention (EPR) effect, which is primarily based on size, or to construct dual modality systems. However, negative effects such as hemolysis, platelet activation and aggregation, generation of reactive nitrogen and oxygen species, leucocyte activation and adhesion and complement activation have been described for nanocarriers aimed at the vascular system [180,181,182,183]. This problem arises from the fact that the nano-targeted vascular system contains large amounts of platelets near the vascular wall and the platelet activating effect of microparticles has been known for almost 50 years [184].…”
Section: Discussionmentioning
confidence: 99%